2020
DOI: 10.12968/ajmw.2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control practice among traditional birth attendants in Lagos State, Nigeria

Abstract: Background The World Health Organization has defined a traditional birth attendant as a ‘person who assists the mother during childbirth and initially acquired her skills by delivering babies herself or through apprenticeship to other traditional birth attendants’. It is estimated that over 40 million neonatal deaths occur annually worldwide; some of these deaths are the result of infection, which may be attributed to the practices of traditional birth attendants. In Nigeria, maternal mortality because of puer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Community participation is essential in designing community health programmes during public health outbreaks such as COVID-19, which was highlighted by a study into the willingness and barriers to receive the COVID-19 vaccine among residents in the UK and Nigeria [63]. Adding to a quantitative study of TBAs in Lagos [27], our qualitative interviews with TBAs reflected a desire for more government training to develop knowledge of COVID-19 infection prevention and control. Referral pathways to skilled maternity services could be strengthened through mentoring of TBAs, and increased staffing [64].…”
Section: Maintaining Access To Maternity Care During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Community participation is essential in designing community health programmes during public health outbreaks such as COVID-19, which was highlighted by a study into the willingness and barriers to receive the COVID-19 vaccine among residents in the UK and Nigeria [63]. Adding to a quantitative study of TBAs in Lagos [27], our qualitative interviews with TBAs reflected a desire for more government training to develop knowledge of COVID-19 infection prevention and control. Referral pathways to skilled maternity services could be strengthened through mentoring of TBAs, and increased staffing [64].…”
Section: Maintaining Access To Maternity Care During Covid-19mentioning
confidence: 99%
“…Unskilled but frequently-used birth attendants such as TBAs may offer insight into women's health seeking practices during the COVID-19 pandemic. One quantitative study of TBAs in Lagos during COVID-19 found 37.5% of respondents had inadequate knowledge of infection prevention and control [27]. Therefore, this study aimed to add to the growing evidence base, and explore midwives' and TBAs' experiences of COVID-19 in Lagos, Nigeria to gain insight into improving maternity services and pandemic preparation strategies.…”
Section: Introductionmentioning
confidence: 99%